AN ANALYSIS OF DEIXIS ON ANIES BASWEDAN'S SPEECH ABOUT CONDOLENCES FOR THE CITY OF CHRISTCHURCH, NEW ZEALAND - Jabbar, Dicky Abdul; Haryudin, Acep (PROJECT (Professional Journal of English Education), 2020)
This study aims to identify types of deixis. research focus on speeches conducted by Anies Baswedan in condolences for acts of terrorism that occurred in the city of Christchurch, new zealand, which was uploaded on the Jakarta provincial government on youtube channel. The researchers used qualitative descriptive methods. It starts with searching and downloading videos on Youtube, recording speeches delivered in the video, and analyzing what types of deixis are used. in this study obtained a total of 25 data and all types of deixis used by Anies baswedan in his speech, namely person deixis, place deixis, time deixis, discourse deixis, and social deixis. Keywords:  Deixis, Anies Baswedan’s Speech.